Effect of the lithospheric thermal state on the Moho interface: A case study in South America. (July 2017) - Bagherbandi, Mohammad; Bai, Yongliang; Sjöberg, Lars E.; Tenzer, Robert; Abrehdary, Majid; Miranda, Silvia; Alcacer Sanchez, Juan M.
Abstract: Gravimetric methods applied for Moho recovery in areas with sparse and irregular distribution of seismic data often assume only a constant crustal density. Results of latest studies, however, indicate that corrections for crustal density heterogeneities could improve the gravimetric result, especially in regions with a complex geologic/tectonic structure. Moreover, the isostatic mass balance reflects also the density structure within the lithosphere. The gravimetric methods should therefore incorporate an additional correction for the lithospheric mantle as well as deeper mantle density heterogeneities. Following this principle, we solve the Vening Meinesz-Moritz (VMM) inverse problem of isostasy constrained by seismic data to determine the Moho depth of the South American tectonic plate including surrounding oceans, while taking into consideration the crustal and mantle density heterogeneities. Our numerical result confirms that contribution of sediments significantly modifies the estimation of the Moho geometry especially along the continental margins with large sediment deposits. To account for the mantle density heterogeneities we develop and apply a method in order to correct the Moho geometry for the contribution of the lithospheric thermal state (i.e., the lithospheric thermal-pressure correction). In addition, the misfit between the isostatic and seismic Moho models, attributed mainly to deep mantle density heterogeneities and other geophysical phenomena, is corrected for by applying the non-isostatic correction. The results reveal that the application of the lithospheric thermal-pressure correction improves the RMS fit of the VMM gravimetric Moho solution to the CRUST1.0 (improves ∼ 1.9 km) and GEMMA (∼1.1 km) models and the point-wise seismic data (∼0.7 km) in South America. Graphical abstract: Highlights: Crustal thickness using an isostatic model. A numerical experiment is conducted to determine the Moho depth for the South American tectonic plate including surrounding oceans. Studying disturbing gravity signals and filtering these effects from gravity anomaly to estimate Earth's crustal thickness. Studying on the effect of the non-isostatic effects and lithospheric thermal-pressure correction.